THE AMOUNT OF LYMPHOCYTES BEFORE AND AFTER CEMOTHERAPY IN BREAST CANCER AT ULIN GENERAL HOSPITAL BANJARMASIN - Firdinia Gafuri Dohamid; M. Darwin Prenggono; Dona Marisa (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: Breast cancer is the most common malignancies among woman in Indonesian. One of breast cancer treatment is chemotherapy which resist cancer’s cells to grow. But chemotherapy also cause DNA damage that interfere lymphocyte proliferation. Depletion on lymphocyte counts will increased patient’s susceptibility to opportunistic infection. The aim of this research was to knowing the difference of lymphocyte counts because of chemotherapy on breast cancer patients in general hospital Ulin Banjarmasin. This research was an observational analytic with cross sectional approach. The sampling technique was non-probability sampling followed by consecutive sampling. Total samples were 61 patients that match with inclusion criteria. Paired T-test was used to analyze the hypothesis with the result of pvalue=0.000 (ρ<0.05), that means there’s a significant decrease in the number of lymphocyte counts after receiving chemotherapy in general hospital Ulin Banjarmasin, January 2014 to December 2015 period. Keywords: chemotherapy, lymphocyte, breast cancer